2014
DOI: 10.1007/s10546-014-9919-1
|View full text |Cite
|
Sign up to set email alerts
|

The Third GABLS Intercomparison Case for Evaluation Studies of Boundary-Layer Models. Part B: Results and Process Understanding

Abstract: We describe and analyze the results of the third global energy and water cycle experiment atmospheric boundary layer Study intercomparison and evaluation study for F. C. Bosveld (B) · P. Baas · E. I. F. single-column models. Each of the nineteen participating models was operated with its own physics package, including land-surface, radiation and turbulent mixing schemes, for a full diurnal cycle selected from the Cabauw observatory archive. By carefully prescribing the temporal evolution of the forcings on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 92 publications
4
107
0
Order By: Relevance
“…The LLJ's peak wind speed during a spring night was also underestimated by the WRF model (≈4 m s −1 at the simulated PBL height); this LLJ was highly ageostrophic (≈5 m s −1 higher than the geostrophic wind). These findings corroborate the results from the GABLS3 intercomparison study (Bosveld et al 2014) based on measurements from the Cabauw tower.…”
Section: Low-level Jet (Llj)supporting
confidence: 89%
“…The LLJ's peak wind speed during a spring night was also underestimated by the WRF model (≈4 m s −1 at the simulated PBL height); this LLJ was highly ageostrophic (≈5 m s −1 higher than the geostrophic wind). These findings corroborate the results from the GABLS3 intercomparison study (Bosveld et al 2014) based on measurements from the Cabauw tower.…”
Section: Low-level Jet (Llj)supporting
confidence: 89%
“…The consequences of over-diffusion in the SBL is also shown in the study of a katabatic flow compared to an improved Prandtl model by Grisogono and Belušić (2008). The causes of these features are due not only to turbulence but also to land-surface thermal coupling and radiation divergence (Bosveld et al, 2014). In the GABLS1 experiment, no radiation scheme is used and the surface temperature and boundary conditions are forced, leading to a turbulence-only driven SBL.…”
Section: Motivationmentioning
confidence: 92%
“…Previous GABLS studies Svensson et al, 2011;Bosveld et al, 2014) have shown that the representation of the SBL between NWP models is highly variable. In many cases, mixing in models is too large compared to LESs and observations, with numerous consequences as discussed in Section 1.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent paper by Bosveld et al (2014b) deals with the inter-comparison of nineteen single-column models from eleven institutes with field data. Twelve of the models participated also in GABLS2.…”
mentioning
confidence: 99%